Sistem Informasi Pemesanan Makanan/Minuman pada Coffee Hitam Putih Berbasis Web - Sinaga, Nillasari; Nainggolan, Rena; Harianja, Eva Julia Gunawati (Universitas Methodist Indonesia, 2025)
Currently, Coffee Hitam Putih still uses manual recording. Manual order recording is less efficient in terms of time and cost. So, to realize consumer satisfaction in ordering food, a food/beverage ordering information system on web-based Coffee Hitam Putih was created. This information system provides a list of food menus, prices, descriptions, and availability. This information system makes it easier for the management of Coffee Hitam Putih to provide effective and efficient services. It can produce fast, precise and accurate information because it uses a database. The methods used in data collection are: a. Literature method, which is a method of collecting data with the help of books from the library or documents and reports related to this research. b. The observation method, which is observing the running system directly on the object to be studied, in order to provide clear and precise information about the process and activities related to ordering menus at Coffee Hitam Putih. c. Interview method, namely conducting questions and answers directly with the manager of Coffee Hitam Putih. The advantage of this technological development is that it is very helpful for people's daily activities. The existence and role of information technology in all sectors of life have an impact on the economic, social, and cultural aspects of human beings.